2008
DOI: 10.1080/00952990701202954
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of Post-Detoxification Anhedonia: Influence of Clinical and Psychosocial Variables

Abstract: Anhedonia, or the inability to experience pleasure, may be regarded either as a temperamental trait or as a state symptom of negative schizophrenia or melancholic depression. In substance use disorders, anhedonia was linked to hypoactivity of the dopaminergic mesolimbic system during protracted withdrawal. The authors investigated the influence of recent clinical and social-environmental factors on the hedonic capability and related psychopathology in a sample of 70 patients manifesting substance dependence (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…By contrast, we found that depressive symptoms were nearly twice as high in DD and over one and a half times higher in SUD compared to SCZ patients. This finding is in line with research showing that substance abuse is a risk factor for the development of depression (Lynskey et al, 2004; Falck et al, 2006; Pozzi et al, 2008) as well as with our meta-analysis of 3283 patients showing that addicted schizophrenia patients experience more severe depressive symptoms compared to non-abusing patients (Potvin et al, 2007). At study endpoint, depression scores were persistently elevated in DD patients.…”
Section: Discussionsupporting
confidence: 91%
“…By contrast, we found that depressive symptoms were nearly twice as high in DD and over one and a half times higher in SUD compared to SCZ patients. This finding is in line with research showing that substance abuse is a risk factor for the development of depression (Lynskey et al, 2004; Falck et al, 2006; Pozzi et al, 2008) as well as with our meta-analysis of 3283 patients showing that addicted schizophrenia patients experience more severe depressive symptoms compared to non-abusing patients (Potvin et al, 2007). At study endpoint, depression scores were persistently elevated in DD patients.…”
Section: Discussionsupporting
confidence: 91%
“…Although anecdotal reports have long noted the significance of this aspect of the abstinence syndrome, recent clinical studies have used a number of assessment instruments to better quantify the subjective anhedonic/dysphoric state that endures throughout the protracted abstinence phase (Janiri et al 2005; Martinotti et al 2008; Pozzi et al 2008). Animal studies examining this topic are quite limited.…”
Section: Modeling Human Withdrawal Phenotypes In Animalsmentioning
confidence: 99%
“…The influence of recent clinical and social-environmental factors on hedonic capability and related psychopathology were investigated in a study by Pozzi et al (2008). This study was conducted on a sample of 70 patients manifesting dependence on alcohol, opiates, or multiple drugs, without severe comorbidity.…”
Section: Anhedonia In Substance Dependence Disordersmentioning
confidence: 99%
“…What emerged from the previously cited studies is that, in subjects with a substance use disorder, there is a correlation between anhedonia, craving (Janiri et al, 2005), intensity of withdrawal symptoms (Martinotti et al, 2008a), and psychosocial and personality characteristics (Martinotti et al, 2008b; Pozzi et al, 2008). Furthermore, anhedonia and dysphoric mood are associated with the hypoactivity of the dopaminergic system (Guyon et al, 1993; Jaffe et al, 1997; Volkow et al, 1997; Martin-Soelch et al, 2001; Schmidt et al, 2001; Melis et al, 2005).…”
Section: The Treatment Of Anhedoniamentioning
confidence: 99%